Measurement of radar properties of concrete for in situ structural elements - Shaari, A.; Millard, S. G.; Bungey, J. H. (British Institute of Non-Destructive Testing, Northampton, 2002)
Interpretation of ground penetrating radar (GPR) surveys applied to concrete structures requires a prior knowledge of the dielectric properties of the concrete under investigation. Most GPR systems used for field investigations produce a broadband pulse, incorporating frequencies between 100 MHz to 1 GHz and above. A traditional laboratory method of measuring the dielectric properties of concrete at one particular frequency is to use a transmission line system. Measurements can be repeated over a range of discrete frequencies. However, this technique can only be used on special laboratory conditioned specimens. A novel method discussed in this paper uses a broadband GPR pulse, reflected from two discrete reinforcing bar targets within an in situ concrete slab to produce the dielectric properties of the concrete over the broadband spectrum of the antenna. Results of the two methods are compared and possible implications for field measurements are discussed.